Effects of saline-alkali stress on seed germination of Haloxylon ammodendron and Nitraria roborowskii Kom in Qaidam Basin. (4th July 2021) - Xu, Te; He, Kangning; Wang, Hui; Wang, Weilu; Zhang, Tan
ABSTRACT: Haloxylon ammodendron and Nitraria roborowskii Kom are dominant groups characterised in Qaidam Basin. Elucidating the salt-tolerant mechanism of these two plants, which can grow successfully in this desert area affected by salinity and alkalinity, contributes to the protection and restoration of local vegetation. In this paper, seed germination feature responses in saline-alkali conditions were tested. H. ammodendron seeds retained 72% of germination percentage (GP) under high salinity up to 500 mmol L −1 saline solution and other germination parameters showed a significant decrease under increasing salinity without alkaline stress ( P < 0.05). GP of N. roborowskii Kom was significantly accelerated from 0 to 200 mmol L −1 saline solution ( P < 0.05), while other germination parameters were significantly accelerated from 0 to 100 mmol L −1 saline solution without alkaline stress ( P < 0.05). Germination parameters of H. ammodendron under low concentration (concentration < 300 mmol L −1 ) alkali stress (pH < 8.78) were accelerated than non-alkali stress. Germination parameters of N. roborowskii Kom seeds were significantly inhibited under alkali stress ( P < 0.05); moreover, the facilitation of low salinity was diminished by alkali stress ( P < 0.05). The regression models of germination parameters and salinity under different pH values presented cubic curves, quadratic curves, and linear model and all models were significant ( P < 0.05) in both plants.